2007
DOI: 10.1890/0012-9658(2007)88[37:aoifdf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Island Food-Web Dynamics Following Major Disturbance by Hurricanes

Abstract: Major abiotic disturbance can be an important factor influencing food-web dynamics, particularly in areas impacted by the recent increase in hurricane activity. We present a unique set of data on key food-web processes occurring on 10 small islands for three relatively calm years and then four subsequent years during which two hurricanes passed directly over the study site. Herbivory, as measured by leaf damage, was 3.2 times higher in the year after the first hurricane (2000) than in the previous year and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 38 publications
1
63
2
5
Order By: Relevance
“…Previously, we showed that herbivory increased markedly in Abaco following hurricane disturbance and suggested that this was caused by a reduction of many predatory species, including lizards, spiders and parasitoids (Spiller and Schoener 2007). Hence, hurricane disturbance associated with extremely high rainfall may devastate predators in multiple trophic levels simultaneously and thereby decrease the overall trophic interaction strength of predators on herbivores, as in the descending portion of Fig.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previously, we showed that herbivory increased markedly in Abaco following hurricane disturbance and suggested that this was caused by a reduction of many predatory species, including lizards, spiders and parasitoids (Spiller and Schoener 2007). Hence, hurricane disturbance associated with extremely high rainfall may devastate predators in multiple trophic levels simultaneously and thereby decrease the overall trophic interaction strength of predators on herbivores, as in the descending portion of Fig.…”
Section: Discussionmentioning
confidence: 86%
“…In 1999, the year with highest June-November rainfall, Floyd (a category IV hurricane) passed directly over the study site in September and the storm surge completely inundated all the study islands; all free-living lizards apparently died or were washed away (Schoener et al 2001). The islands were "repopulated" by hatchlings emerging from eggs that survived the storm surge, but lizard densities in the following spring were still much lower than before the hurricane (Spiller and Schoener 2007). In 2001, the second highest rainfall year, the surge from Michelle again completely or largely inundated the study islands and lizard densities declined (Schoener et al 2004;Spiller and Schoener 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to the outbreak of insect herbivores following Hurricane Hugo (Torres 1992), we found that changes in the abundance of chrysomelids (herbivorous beetles) were not correlated with the general increase in the amount of foliage near the ground. Both increases and decreases in the abundance of herbivorous insects post-cyclone have been observed (Schowalter and Ganio 1999;Barberena-Arias and Aide 2002;Angulo-Sandoval et al 2004) and the reasons for inconsistent results may be related to predator control (Spiller and Schoener 2007).…”
Section: Discussionmentioning
confidence: 95%